2005
DOI: 10.1111/j.1532-5415.2005.53250.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cytomegalovirus Infection and Inflammation Are Associated with Prevalent Frailty in Community‐Dwelling Older Women

Abstract: See editorial comments by Dr. Kevin P. High on pp 906-908) OBJECTIVES: To evaluate the association between asymptomatic chronic cytomegalovirus (CMV) infection and the frailty syndrome and to assess whether inflammation modifies this association. DESIGN: Cross-sectional analysis. SETTING: Women's Health and Aging Study I & II, Baltimore, Maryland. PARTICIPANTS: Seven hundred twenty-four communitydwelling women aged 70 to 79 with baseline measures of CMV, interleukin-6 (IL-6), and frailty status. MEASUREMENTS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
168
4
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(190 citation statements)
references
References 42 publications
7
168
4
8
Order By: Relevance
“…Additionally, recent studies have associated chronic CMV infection with prevalent frailty, a state with increased morbidity and mortality in older adults 24,25 . Ghana must introduce the provision of CMV seronegative blood product support to the above stated vulnerable individuals as soon as possible, since this has been the standard of care since the late 1980s in most developed countries after studies showed this strategy significantly reduced the rate of TT-CMV [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent studies have associated chronic CMV infection with prevalent frailty, a state with increased morbidity and mortality in older adults 24,25 . Ghana must introduce the provision of CMV seronegative blood product support to the above stated vulnerable individuals as soon as possible, since this has been the standard of care since the late 1980s in most developed countries after studies showed this strategy significantly reduced the rate of TT-CMV [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…CMV is a candidate causative agent for this activation as it chronically infects people lifelong, from newborns to centenarians. Chronic CMV infection is also associated with prevalent frailty, a state with increased morbidity and mortality in older adults (25). Accordingly, we have evaluated functional T cell responses to peptides spanning two CMV immunogenic proteins, pp65 and IE-1, in 65 chronically infected subjects aged 25-100 years.…”
Section: Discussionmentioning
confidence: 99%
“…An evolving definition of inflammation in gerontology is low-grade activation of the innate immune system, leading to chronic production of inflammatory mediators. Inflammatory processes in general have been implicated as predictors of or contributors to chronic diseases and conditions of aging (117), such as cardiovascular disease (118), low cognitive performance (119), osteoarthritis and dementia (120), frailty (121,122), muscle wasting (123), physical performance (123,124), disability (125,126) and mortality (127)(128)(129). These associations have been…”
Section: The Biological Explanationmentioning
confidence: 99%